REVIEWING RELIGIOUS UNDERSTANDING OF THE MARRIAGE HADITH - Nurul Nurul; Mochamad Tholib Khoiril Waro (Riwayah: Jurnal Studi Hadis, 2022)
Intellectual discourse on women especially on marriage in Islamic tradition are dominated by patriarchal perspective. Islamic Intellectual treasures such as hadith and its explanation, exegesis, books, scholar and their intellectual products showed us how ancient Arabic patriarchal pattern existed. On the other hand, modernity led civilization to the values of equity, equality, human right and democracy against inequity, inequality, monarchy and individual cult. Problems of inequity appeared much on women discourse in Islamic tradition. Thousands of hadiths were identified recorded by men in patriarchal culture. It made gender issues in Islamic tradition are still sensitive. This article tries to reconstruct the discourse in one of the popular hadiths in marriage in order to explore the possibility of studying the meaning of a more moderate hadith.  By using Juynboll's common link, the author finds the hadith narrowed to one name, namely A'masy which is then categorized as a common link in this study.  In addition to having implications for the emergence of certain names as common links, this study also reviews further implications regarding the relevance of broader studies in hadith studies; urgent efforts to be made in order to place hadith as a source of more contextual and moderate religious discourse.